The secret of chimneys. - Christie, Agatha, 1890-1976. (London, Bodley Head, 1925)
Agreeing to take on a simple errand for a friend by delivering the scandalous memoirs of a recently deceased European count to a London publisher, Anthony Cade steps right into a case of international intrigue designed to restore the country's monarchy that culminates in a terrible murder and a stunning revelation.
Mode of access: Internet.
Keywords: Superintendent Battle -- (Fictitious character); Police; Murder -- Investigation; Conspiracies; Meurtre -- Enquêtes -- Romans, nouvelles, etc; Conspiration -- Romans, nouvelles, etc; Police -- Fiction; Murder -- Investigation -- Fiction; Conspiracies -- Fiction; Battle, Superintendent (Fictitious character) -- Fiction; Fiction